ACTIVITIES OF MICRO-, SMALL AND MEDIUM-SIZED ENTERPRISES OF UKRAINE DURING THE WAR: CHALLENGES AND DEVELOPMENT TRENDS - Vlasenko, Iryna; Sirenko, Svitlana; Ternova, Alla (European Science, 2025)
The dynamics of the performance indicators of large, medium, small and micro-enterprises is considered. An analysis of the performance indicators of Ukrainian enterprises in comparison with the pre-war period is presented. It is shown that despite the dev